Enhancing student's higher order thinking skills (HOTS) through the socratic method approach with technology - Md. Suhadi, Salihuddin (2015)
Technologies have a potential to make learning more dynamic and capable of going beyond traditional learning boundaries. With the use of online technologies for example, students can interact with teachers and other students, regardless of time and distance. The learning process can also occur in synchronize or asynchronies. Meaningful interaction is needed in the Socratic method of learning because this is the concept of learning through question after question to build knowledge. The dialogue interaction, questions are either verbal or non-verbal. So this is where online technology comes into allows students to always dialogue with certain individuals to construct new knowledge. Next, by using the Socratic method of learning the high level of HOTS can be increased which is emphasized in the field of education in Malaysia nowadays. This paper will discuss previous studies about the potential of technology in engineering methods to improve student’s HOTS.